2017
DOI: 10.1590/0001-3765201720160500
|View full text |Cite
|
Sign up to set email alerts
|

Beef Tallow and Emulsifier in Growing-Finishing Pig Diets

Abstract: Two trials were aimed to evaluate beef tallow in diets with and without emulsifier on performance of pigs at growing-finishing phases. In the first trial, 15 barrows (22.03±0.62 kg) were distributed among three treatments: reference diet; test diet 1 (5% beef tallow) and test diet 2 (10% beef tallow). Beef tallow presented average value of 7130.97 kcal ME/kg. For the performance trail, 30 barrows (24.85±1.18 kg) were distributed among five treatments: T1 -diet with soybean oil and 3230 kcal ME /kg; T2 -diet wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Emulsifier-like feed additives have been widely used in terrestrial animals [1][2][3][4][5][6]. In recent years, they are also being more and more frequently used in farmed fish, typically bile acids [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Emulsifier-like feed additives have been widely used in terrestrial animals [1][2][3][4][5][6]. In recent years, they are also being more and more frequently used in farmed fish, typically bile acids [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies reported that the improvement in energy harnessing with the use of emulsifiers occurs due to the greater digestibility of the ether extract. According to Santos et al (2017), the beef tallow had higher digestibility for pigs when the animals received emulsifier supplementation, therefore increasing the diet's energy harnessing.…”
Section: Discussionmentioning
confidence: 99%